2012
DOI: 10.2478/v10222-011-0038-0
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Properties, Acrylamide Content and Sensory Quality of Ginger Cakes with Different Formulations

Abstract: Key words: rye fl our, extraction rate, white wheat fl our, ginger cake, antioxidant capacity, phenolic acids profi le, acrylamide content, sensory qualityThe antioxidant capacity, phenolic acids profi le, acrylamide contents and sensory quality of ginger cakes formulated on dark and brown rye fl ours according to the traditional formula (type 1 and type 2), and on the mixed white wheat fl our with dark and brown rye fl ours due to the currently used formulation (type 3 and type 4), were studied. The antioxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…A similar increasing trend of antioxidant capacity vs. rutin addition was found for rye-buckwheat ginger cakes with dough fermentation step ( Table 2). The antioxidant capacity determined by DPPH test for rye-buckwheat ginger cakes was higher compared to ginger cakes from dark rye or brown rye flours [Zieliński et al, 2012].…”
Section: Antioxidant Capacity Provided By Dpph Assay and CV Methodsmentioning
confidence: 73%
See 1 more Smart Citation
“…A similar increasing trend of antioxidant capacity vs. rutin addition was found for rye-buckwheat ginger cakes with dough fermentation step ( Table 2). The antioxidant capacity determined by DPPH test for rye-buckwheat ginger cakes was higher compared to ginger cakes from dark rye or brown rye flours [Zieliński et al, 2012].…”
Section: Antioxidant Capacity Provided By Dpph Assay and CV Methodsmentioning
confidence: 73%
“…It can be suggested that the application of buckwheat flours in ginger cake formula was more effective in antioxidant activity increase in comparison to ginger cakes from dark rye or brown rye flours [Zieliński et al, 2012].…”
Section: Antioxidant Capacity Provided By Dpph Assay and CV Methodsmentioning
confidence: 99%
“…A 6-member trained panel judged ginger cakes in a 10-point scale (0—for weak, 10—for very good) using Quantitative Descriptive Analysis (QDA) to determine differences between each type of biscuits. The description of sample preparation and standardized procedure of sensory evaluation were in details presented by Zieliński et al [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, there is a constant flow of new product initiators in food product development center which claim to be "functional foods" or "foods with additional strength welfares" but only a few of them proved to be successful [13]. Food industries are nowadays encrusting enormously challenges from which the most imperative is around the necessity to develop new products which can subsidize to the customer's aspiration for a health-defensive diet and the industries are successful to achieve this task because they mainly focused on the natural foods that have antioxidant potential [14].…”
Section: Introductionmentioning
confidence: 99%